2016
DOI: 10.1021/acs.jced.6b00034
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior and Thermophysical Properties of Peace River Bitumen + Propane Mixtures from 303 K to 393 K

Abstract: Propane and mixtures including propane as a principal component are among the leading potential candidates for co-injection along with steam for improving the process and environmental efficiency of oil sands bitumen production processes. Phase diagrams and thermophysical property data enable technologies for the development and optimization of such processes. In this work, phase behavior, phase composition, and phase densities of propane + Peace River bitumen mixtures are reported in the temperature range 303… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…Badamchi-Zadeh et al (2009a) and Jossy et al (2009) observed VL and LL boundaries for propane diluted bitumen but did not measure phase compositions. Dini et al (2016) also observed VL and LL regions and predicted a VLL boundary.…”
Section: List Of Figures and Illustrationsmentioning
confidence: 82%
See 4 more Smart Citations
“…Badamchi-Zadeh et al (2009a) and Jossy et al (2009) observed VL and LL boundaries for propane diluted bitumen but did not measure phase compositions. Dini et al (2016) also observed VL and LL regions and predicted a VLL boundary.…”
Section: List Of Figures and Illustrationsmentioning
confidence: 82%
“…Both VL and LL regions were observed for mixtures of bitumen and propane (Badamchi-Zadeh et al, 2009a;Jossy et al, (2009); Nourozieh et al, 2015). Dini et al, (2016) also observed VL and LL regions and predicted a VLL boundary. They identified the two liquid phases as a solvent/maltene-rich and a bitumen-rich phase.…”
Section: Bitumen/n-alkane Phase Regionsmentioning
confidence: 94%
See 3 more Smart Citations